A self-assembled 3D Go-Col composite scaffold for tissue engineering - Girão, André (2018)
A portfolio of Graphene Oxide-Collagen (GO-Col) composite scaffolds was prepared and submitted to mechanical and swelling tests in order to select the most suitable candidate for tissue engineering applications. The optimal GO-Col scaffold composition and its reduced contra-part were then tested as promising materials for cell culture assays.